High Risk of Mismatch Between Sanders and Risser Staging in Adolescent Idiopathic Scoliosis: Are We Guiding Treatment Using the Wrong Classification?. Issue 2 (February 2020) - Minkara, Anas; Bainton, Nicole; Tanaka, Masashi; Kung, Justin; DeAllie, Christopher; Khaleel, Alexandra; Matsumoto, Hiroko; Vitale, Michael; Roye, Benjamin
Abstract : Background: Despite known limitations, Risser staging has traditionally been the primary marker of skeletal maturity utilized in decision-making for treatment of adolescent idiopathic scoliosis (AIS). The purpose of this study is to assess the incidence and factors associated with mismatch between Risser Staging and Sanders classification, and determine interobserver reliability. Methods: We reviewed the medical records of consecutive patients aged 10 to 18 referred to our institution for evaluation of AIS from January to June 2016 with a closed triradiate cartilage. Data collected included sex, age, race, height, weight, body mass index percentile, menarchal status, Risser stage, Sanders classification, and major curve. Risser and Sanders stage was determined by 2 fellowship-trained pediatric spine surgeons and 1 pediatric orthopaedic nurse practitioner. Mismatch was defined as Risser stage 2 to 4 corresponding to Sanders 3 to 5, and Risser 0 to 1 corresponding to Sanders 6 to 7. Results: A total of 165 consecutive patients were identified (mean age: 13.9±1.7 y, major curve 28.2±15.4 degrees, 76% female). The risk of skeletal maturity mismatch, based on the criteria of Risser 2 to 5 (limited growth remaining) corresponding to Sanders 3 to 5 (significant growth remaining) was 21.8%, indicating that 1 of 5 patients would be undertreated if managed by Risser criteria. Conversely, the mismatch risk for Risser 0 to 1 corresponding to Sanders 6 to 7 was 3.6%, leading such patients to be treated conservatively longer than necessary. Males and those of Hispanic ethnicity were at a higher risk of mismatch (23.1% vs. 11.9%, P =0.08; 33.3% vs. 8.8%, P =0.04, respectively). Body mass index percentile, race, and major curve were not associated with mismatch. The unweighted and weighted interobserver κ for Risser staging was 0.74 and 0.82, respectively, and 0.86 and 0.91 for Sanders classification, respectively. Conclusion: Given the limited sensitivity of Risser staging during peak growth velocity, high mismatch risk, and lower interobserver reliability, the Sanders classification should be utilized to guide treatment options in patients with AIS. Compared with Sanders, utilizing Risser staging results in mistreatment in a total of 1 of 4 patients, with the vast majority being undertreated. Level of Evidence: Level II.